2022
DOI: 10.1007/s13555-022-00730-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Noninvasive 1060-nm Diode Laser for Medial Knee Fat Reduction

Abstract: Introduction Laser lipolysis is a rapidly growing noninvasive body-contouring treatment in Asians. There is increasing demand for leg contouring, especially in areas where unwanted fat deposits are prominent despite diet and exercise. Medial fat knees are one of the esthetic concerns of women today and can be a challenging problem in terms of treatment. There are few noninvasive options to remove fat from these areas. This study aims to evaluate the safety and efficacy of a 1060-nm diode laser for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The laser raises the temperature of adipose cells between 42°C and 47°C, damaging their structural integrity. 24 After the treatment session, the body naturally eliminates the disrupted cells over the next few months. 24 Disrupted fat cells are permanently eliminated from the body and will not regenerate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The laser raises the temperature of adipose cells between 42°C and 47°C, damaging their structural integrity. 24 After the treatment session, the body naturally eliminates the disrupted cells over the next few months. 24 Disrupted fat cells are permanently eliminated from the body and will not regenerate.…”
Section: Discussionmentioning
confidence: 99%
“…24 After the treatment session, the body naturally eliminates the disrupted cells over the next few months. 24 Disrupted fat cells are permanently eliminated from the body and will not regenerate. Previous studies on 1060-nm diode lasers showed significant reductions in localized subcutaneous fat on the abdomen 15 and flanks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations